Cognitive Effects of Thinking Hats and Taxonomy Bloom on Indigenous Pupils in Malaysia - Ramle, Abdullah; Yeoh, Sun Wei; Abdul Razaq, Ahmad; Chew, Fong Peng (2018)
The role of metacognitive skills becomes crucial in current learning process, particularly independent of intelligence. Pupil understands own thinking in the metacognitive process, they aware how their brain process information. The awareness helps them to develop an effective strategy in learning. According to Gardner’s multiple intelligence theory, implementation of metacognitive skills enable student to discover their own intelligence and select the most effective learning method to maximize the learning outcomes. This is a quantitative research to evaluate the effectiveness of using different thinking tools to enhance pupil’s cognitive level. There are 3 thinking tools in this research, Thinking Maps, Six Thinking Hats and Taxonomy Bloom. This research will focus on the indigenous pupils because they are the at-risk group in the trend of modernization.